Implementation architecture of mimic security defense based on SDN - Zhen-peng WANG; Hong-chao HU; Guo-zhen CHENG; Chuan-hao ZHANG (网络与信息安全学报)
To deal with the attacks employing unknown security vulnerabilities or backdoors which are difficult for traditional defense techniques to eliminate,mimic security defense (MSD) that employs “dynamic,heterogeneity,redundancy (DHR)” mechanism can increase the difficulty and cost of attack and uncertainty of system so as to improve network security.Based on the software defined networking (SDN),an implementation architecture of MSD was proposed.First,diverse functional equivalent variants for the protected target were constructed,then leverage the rich programmability and flexibility of SDN to realize the dynamic scheduling and decision-making functions on SDN controller.Simulation and experimental results prove the availability and the intrusion tolerant ability of the architecture.